Characterising smart initiatives' planning in Smart Cities: an empirical analysis in Spanish Smart Cities - Rodriguez-Bolivar, Manuel Pedro; Alcaide Muñoz, Cristina; Alcaide Muñoz, Laura (ACM International Conference Proceeding Series, 2021)
City governments around the world are turning cities into smart ecosystems, undertaking a great bulk of smart initiatives in different domains with the aim at improving efficiency in public services and making city governments more transparent and accountable. Some smart projects implemented in different domains are considered as isolated islands not included in a strategic planning of the city. By contrast, other cities have felt an urgent need for undertaking integrated smart projects into a holistic strategic planning in order to avoid fragmentation. This this paper aims to investigate the smart city phenomenon and its current strategic planning practices on smart projects. In order to do so, the study reported in this paper places smart city strategies and planning approaches of smart projects in a number of the Spanish smart cities under the microscope. Findings show that demographic and political attributes can be attributes that influences on the design of patterns in strategic planning of smart projects.
Keywords: smart cities; smart initiatives; smart projects; strategic planning; Scopus(2)